(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2015)
The present study was conducted to evaluate the effects of respiratory gases on shelf life of fresh Oyster mushrooms. The complete randomize design was followed for the experiment. After sorting of collected cultivated mushrooms were packed in different polymeric packaging materials-polystyrene trays over wrapped with polyvinyl chloride (PVC) microfilm and polypropylene (PP) at refrigerated and ambient temperature condition for 12 days. Gas composition as CO2, O2, N2, concentration at 3 days intervals of the total 12 days duration also including sensorial quality were evaluated. CO2 contents were found to be increased but O2 contents was found to be reduced for both packaging materials within 3 days storage at ambient temperature. In refrigerator, oxygen content in both of trays increased sharply within 3 days of storage. Off flavor appeared strongly and started to spoil from third days after Oyster mushrooms packed in ambient temperature, which on the contrary was not detected in mushroom packed and stored until 12 days in refrigerator. Shortest storage period for a single day at ambient condition and extended period of 12 days self life was determined when mushrooms were stored in refrigerator in respect of sensorial quality in sealed polypropylene bag or in polystyrene trays. Bangladesh J. Sci. Ind. Res. 50(3), 205-210, 2015